Peripheral arthritis as a form of atypical presentation of a multiple myeloma - Leymer Carlos Aliaga Carrazana; Roxana González-Figueredo; Melissa Emilia Hevia-Surós; Maricelis Virgen Carrazana-Ayala (Universidad de Ciencias Médicas de Granma, 2020)
Multiple myeloma is a malignant neoplasm of plasma cells characterized by bone marrow infiltration and extensive skeletal destruction resulting in anaemia, pain in the bone and fractures. It represents 1% of malignant tumours and a little more than 10% of all malignant hemopathies. Case report: We present the case of a 69-year-old patient, urban origin, with a personal pathological history of arterial hypertension and osteoarthrosis. He goes to the Internal Medicine service for presenting pain in the joints of both upper and lower limbs, of great intensity and long duration accompanied by fatigue that he relieves with analgesics. Complementary examinations showed haemoglobin figures of 105 g/L, erythrocyte sedimentation 131 mm/h, as well as Kappa and Lambda, increased with Bence Jones protein of 1,365 g/24h. Plain X-ray and plain CT scan of the chest ruled out lung neoplasia and bone lesions. The myelogram concluded with a diagnosis of multiple myeloma. Conclusions: although osteolytic lesions, with the pain of the axillary skeleton, are the form of presentation of multiple myeloma, it does not exclude that the non-appearance of bone lesions, the presence of osteosclerosis or peripheral arthritis may be another form of presentation. In addition, the patient's comorbidities are considered a clinical element to suspect atypical or uncommon presentations of the disease.